2015
DOI: 10.1002/jcsm.12039
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenic obesity and myosteatosis are associated with higher mortality in patients with cirrhosis

Abstract: Background and aimsObesity is frequently associated with cirrhosis, and cirrhotic patients may develop simultaneous loss of skeletal muscle and gain of adipose tissue, culminating in the condition of sarcopenic obesity. Additionally, muscle depletion is characterized by both a reduction in muscle size and increased proportion of muscular fat, termed myosteatosis. In this study, we aimed to establish the frequency and clinical significance of sarcopenia, sarcopenic obesity and myosteatosis in cirrhotic patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
462
4
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(487 citation statements)
references
References 39 publications
14
462
4
7
Order By: Relevance
“…[8][9][10][11][12][13] While some of these models are helpful in predicting posttransplant outcomes, none of these scores include information on the recipient's BC. While some studies have recently reported an association of sarcopenia with clinical outcome in cirrhosis and orthotopic liver transplantation (OLT), 15,[19][20][21][22][23] the prognostic value of muscle quality (skeletal muscle density and myosteatosis) compared to muscle quantity (skeletal muscle mass-SMM, as the morphological aspect of sarcopenia) remains to be determined. 2,15 The importance of nutritional status and its assessment in patients with chronic liver disease are further highlighted by the recent European Association for the Study of the Liver (EASL) and American Association for the Study of Liver Diseases (AASLD) guidelines on nutrition in chronic liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13] While some of these models are helpful in predicting posttransplant outcomes, none of these scores include information on the recipient's BC. While some studies have recently reported an association of sarcopenia with clinical outcome in cirrhosis and orthotopic liver transplantation (OLT), 15,[19][20][21][22][23] the prognostic value of muscle quality (skeletal muscle density and myosteatosis) compared to muscle quantity (skeletal muscle mass-SMM, as the morphological aspect of sarcopenia) remains to be determined. 2,15 The importance of nutritional status and its assessment in patients with chronic liver disease are further highlighted by the recent European Association for the Study of the Liver (EASL) and American Association for the Study of Liver Diseases (AASLD) guidelines on nutrition in chronic liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed low or declining muscle mass is emerging as a negative prognostic factor associated with higher morbidity and mortality in obese patients with chronic diseases [67,68]. Obese individuals with gastrointestinal cancers and low muscle mass accordingly had higher risk of dying than matched obese patients without muscle abnormalities [68]. In obese heart failure patients, low physical capacity also predicted poor outcome [62].…”
Section: Introduction: What We Knowmentioning
confidence: 99%
“…This could appear as contradictory to the so-called ‘obesity paradox', but it means that obesity does not protect from chronic disease-related mortality when it is associated with sarcopenia. Indeed low or declining muscle mass is emerging as a negative prognostic factor associated with higher morbidity and mortality in obese patients with chronic diseases [67,68]. Obese individuals with gastrointestinal cancers and low muscle mass accordingly had higher risk of dying than matched obese patients without muscle abnormalities [68].…”
Section: Introduction: What We Knowmentioning
confidence: 99%
“…7 Sarcopenic obesity, severe muscle depletion in the setting of obesity, is reported in 30% to 42% of obese patients with cirrhosis 810 and is associated with increased risk of pre-LT mortality. 9,11,12 Unfortunately, studies evaluating waitlist and post-LT outcomes do not use unified criteria for defining obesity or sarcopenia in this unique population, which may lead to discrepant results. Given the many limitations of BMI as a measure of obesity-related risk in liver transplant candidates, we recommend against its use as the sole measure of obesity in this population.…”
Section: Pretransplant Considerationsmentioning
confidence: 99%